IMPLEMENTASI LEAN SIX SIGMA UNTUK MENGURANGI PRODUK CACAT PADA PROSES PEMBUATAN KACA - Gayuh Lemadi; dian eko adi prasetio; Alim Wulandara (Fakultas Sains Dan Teknologi, 2024)
Cipta Kreasi Prima Mandiri is a company operating in the manufacturing sector which produces glass products. The increasingly competitive level of competition currently requires a company to process all its resources optimally and make improvements intensively and efficiently. However, in reality PT. Cipta Kreasi Prima Mandiri still produces 45,727 units of defective products every year and there is waste during production, such as non-value added activities. Based on the problems above, improvements need to be made to overcome them. In this research, the first step taken was to create a Value Stream Mapping and determine the CTQ standards for the company. Based on the calculation of the process capability index, the result was 0.76. Calculating the company's DPO value, the value obtained is 0.0024. Calculating the DPMO value, the value obtained is 2445. After these calculations, the company's sigma level value is known to be 3.99. The results of this research were that the process capability assessment criteria were obtained with the glass manufacturing process capability still being low. After it was discovered that this capability was still low, an analysis step was carried out which obtained the results that defective products were mostly caused by human factors. Therefore, corrective steps are needed that are in accordance with the company's problems to improve product quality and achieve a sigma value of 4.5 in the next year.